MORFOLOGÍA CRANEOFAOAL EN PADRES DE NIÑOS CON LABIO Y PALADAR HENDIDO (2018)
Purpose: To identify in the parents the cephalometric parameters that can be used to predict the chance of having children with lip and/or cleft palate.Material and Methods: it was a descriptive observational study, with sample of 83 fathers and mothers of children with orofacial clefting that attended the Fundación Operación Sonrisa in Bogotá and Bucaramanga, and 23 fathers and mothers of children without orofacial clefting that lived in Bucaramanga. To each one a lateral x-ray was taken and 12 linear and angular measures were analyzed. In order to compare the cephalometric measurements between the groups test t of Student was applied. To compare between both ANOVA and training groups to compare the averages of cephalometric measures by type of orofacial clefting, considering a level of significance of α =0.05.Results: The cephalometric measures that were different between the two groups were: Co - To, ENA - ENP, Go - Me, S - N, angle SNB and all were diminished of statistically significant difference (P < 0.05) in the group of mothers whose children registered lip and cleft palate. There were no statistically significant differences in the measures of the fathers.Conclusion: A greater maternal genetic interference in the craniofacial morphology could be suggested.